The Impact of Illegal Mining on Environmental Conservation - Marisyah Taher (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The legal issues in this paper are regarding mining activities that are not licensed and have various impacts on the community and life around the mining site, including; environmental damage, high levels of pollution (soil, water and air), also cause disruption to the wider community, especially as a result of blasting activities carried out to open mine sites and not re-doing reclamation. Disruption of aspects of people's lives, when viewed from the side of Human Rights (HAM), namely especially those related to economic, social and cultural rights, is of course very much in touch with the impact of this coal mining. Because human rights include aspects of the right to live and live a good, safe and healthy life which is the right to a good and healthy environment regulated in the 1945 Constitution of the Republic of Indonesia.